Propyl gallate induces human pulmonary fibroblast cell death through the regulation of Bax and caspase-3 - Woo Hyun Park (Annals of Medicine, 2024)
AbstractPropyl gallate (PG) has been found to exert an inhibitory effect on the growth of different cell types, including lung cancer cells. However, little is known about the cytotoxicological effects of PG specifically on normal primary lung cells. The current study examined the cellular effects and cell death resulting from PG treatment in human pulmonary fibroblast (HPF) cells. DNA flow cytometry results demonstrated that PG (100–1,600 μM) had a significant impact on the cell cycle, leading to G1 phase arrest. Notably, 1,600 μM PG slightly increased the number of sub-G1 cells. Additionally, PG (400–1,600 μM) resulted in the initiation of cell death, a process that coincided with a loss of mitochondrial membrane potential (MMP; ΔΨm). This loss of MMP (ΔΨm) was evaluated using a FACS cytometer. In PG-treated HPF cells, inhibitors targeting pan-caspase, caspase-3, caspase-8, and caspase-9 showed no significant impact on the quantity of annexin V-positive and MMP (ΔΨm) loss cells. The administration of siRNA targeting Bax or caspase-3 demonstrated a significant attenuation of PG-induced cell death in HPF cells. However, the use of siRNAs targeting p53, Bcl-2, or caspase-8 did not exhibit any notable effect on cell death. Furthermore, none of the tested MAPK inhibitors, including MEK, c-Jun N-terminal kinase (JNK), and p38, showed any impact on PG-induced cell death or the loss of MMP (ΔΨm) in HPF cells. In conclusion, PG induces G1 phase arrest of the cell cycle and cell death in HPF cells through apoptosis and/or necrosis. The observed HPF cell death is mediated by the modulation of Bax and caspase-3. These findings offer insights into the cytotoxic and molecular effects of PG on normal HPF cells.